A probabilistic wavelet-support vector regression model for streamflow forecasting with rainfall and climate information input - Liu, Zhiyong; Zhou, Ping; Zhang, Yinqin (Journal of hydrometeorology, 2015)
It is essential to explore reliable streamflow forecasting techniques for water resources management. In this study, a Bayesian wavelet-support vector regression model (BWS model) is developed for one- and multistep-ahead streamflow forecasting using local meteohydrological observations and climate indices including El Niño-Southern Oscillation (ENSO) and the Indian Ocean dipole (IOD) as potential predictors.
Gesehen am 29.06.2020